Paradigms, Strategies, and Challenges of Quality Control in Higher Education in the Digital Era: A Systematic Literature Review - Giovani Septio; R Madhakomala (Dinasti Publisher, 2025)
Digital transformation demands systemic adaptation in the quality assurance framework for higher education. This study aims to synthesize literature on the paradigms, strategies, and challenges of quality control in the digital era using a Systematic Literature Review (SLR) guided by PRISMA. Thematic analysis was conducted on 39 selected articles from an initial corpus of 80. The main findings show a paradigm evolution towards the